Pengaruh Religiusitas dan Gaya Hidup Terhadap Perilaku Konsumsi Masyarakat Pengguna Go-Food - Novi Yanti; Lika Akana Helmi; Syamsurizal Syamsurizal (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
This research is motivated by changes in consumer behavior in consuming food using Go-food services. The purpose of this research is to analyze the behavior of Muslim consumers in relation to Go-food users, especially the behavior of consumers who live in urban areas. This study will also examine the influence of religiosity and lifestyle on consumer behavior. The method used in this study is a quantitative method, namely by surveying 96 Muslim respondents using Go-Food in Padang City, the area was chosen because it has a dominant Muslim population. The analysis technique uses statistical tests t test, f test, and R2 test. Data processing in this study uses SPSS 22. The results of this study prove that simultaneously Religiosity and Lifestyle have a significant effect on Consumer Behavior. From the f test, the research significance was <0.05 (0.000 <0.05), and f table > f table (13.266 > 3.09). For the religiosity variable, it can be seen that the Sig value shows a number <0.05 (0.000 <0.05), and tcount > ttable (3.775 > 1.989), then Ha is accepted Ho is rejected. For the Lifestyle variable, it can be seen that the Sig value shows <0.05 (0.004 <0.05), and t_count>t_(table) (2.931 >1.989), then Ha is accepted Ho is rejected. The implications of this study show that together the independent variables play an important role in determining consumer behavior. All independent variables can explain their influence on consumer behavior by 20.5% and the remaining 79.5% can be explained by other variables outside this study.